(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The formation of a health culture in primary school students has become an essential aspect of modern pedagogy, particularly in Uzbekistan where educational reforms emphasize the holistic development of children. This paper explores the improvement of methodological approaches aimed at fostering healthy behaviors and attitudes in young learners. The study highlights the role of educators in modeling and reinforcing positive health practices, and considers how curricular integration, interactive teaching techniques, and psychological readiness of teachers contribute to the cultivation of a sustainable health culture. By examining both local and international practices, the paper proposes an enhanced pedagogical framework that supports students’ physical, emotional, and social well-being from an early age. The research uses qualitative and quantitative methods to assess current practices in Uzbek primary schools and evaluates the effectiveness of specific educational interventions. Findings demonstrate that well-structured health education programs significantly influence children’s health literacy, personal hygiene, physical activity, and awareness of safety rules. This work contributes to the ongoing educational discourse by offering practical recommendations to improve the methodology for forming a health culture among primary school pupils.